2007
DOI: 10.1016/j.fertnstert.2006.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Expression of two-pore domain potassium channels in nonhuman primate sperm

Abstract: The results demonstrated expression and function of K(2P) potassium channels in nonhuman primate sperm for the first time. The unique, discrete distributions of K(2P) channels in nonhuman primate sperm suggest specific roles for this subfamily of ion channels in primate sperm function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
3
7
0
Order By: Relevance
“…In addition, a previous study from our laboratory also found these channels to be expressed in bovine ovaries, testis, and germ cells (Hur et al 2009). Furthermore, they were also present in monkeys, where their expression was restricted to sperm (Chow et al 2007). In this study, the patterns of each K 2P channel mRNA expression showed embryo stage-specific effects.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…In addition, a previous study from our laboratory also found these channels to be expressed in bovine ovaries, testis, and germ cells (Hur et al 2009). Furthermore, they were also present in monkeys, where their expression was restricted to sperm (Chow et al 2007). In this study, the patterns of each K 2P channel mRNA expression showed embryo stage-specific effects.…”
Section: Discussionsupporting
confidence: 50%
“…Recent studies have found that K 2P channels are expressed in the mammalian reproductive organ and cells, such as in human cytotrophoblast cells, placental villous tissue and trophoblast cells, myometrium, the placental vascular system, and uterine smooth muscle cells (Bai et al 2005a, 2005b, Tichenor et al 2005, Wareing et al 2006, Chow et al 2007. In addition, a previous study from our laboratory also found these channels to be expressed in bovine ovaries, testis, and germ cells (Hur et al 2009).…”
Section: Discussionmentioning
confidence: 78%
“…This challenge stems from the fact that Trek-1 is known to be insensitive to classical K ϩ channel inhibitors including glibenclamide, 4-aminopyridine, and tetraethylammonium (35,44). Other pharmacological approaches including amiloride, gadolininum, and riluzuole have been criticized as nonspecific (5,18,24,34,43,46). Therefore, to selectively inhibit Trek-1, we created a stable Trek-1 shRNAtransfected MLE-12 cell line.…”
Section: Discussionmentioning
confidence: 99%
“…In reproductive cell types, the presence and function of K 2P channels were also reported (Bai et al 2005a, 2005b, Tichenor et al 2005, Wareing et al 2006, Chow et al 2007. However, the expression and localization of the K 2P channels in bovine germ cells have not yet been reported.…”
Section: Introductionmentioning
confidence: 93%
“…KCNK2 and KCNK4 are also expressed in human uterine smooth muscle, and KCNK2 expression is significantly increased in pregnant term tissues (Tichenor et al 2005). KCNK5, KCNK2, and KCNK4 are expressed by and localized specifically to monkey sperm (Chow et al 2007).…”
Section: Introductionmentioning
confidence: 99%